Development and pilot testing the Family Conference Rating Scale: A tool aimed to assess interprofessional patient-centred communication and collaboration competencies. Issue 5 (28th August 2015) - Dojeiji, Sue; Byszewski, Anna; Wood, Tim
Abstract: There is a paucity of evidence-based literature on the essential communication and collaboration skills to guide health care teams in conducting and assessing their performance in the Family Conference (FC). The authors developed and collected validity evidence for a rating scale of team FC performance, the Family Conference Rating Scale (FCRS). In phase 1, essential FC communication and collaboration skills were identified through a review of existing communication tools and literature on team functioning; a draft 34-item scale was developed. In phase 2, the scale was narrowed to a 6-category, 9-point scale with descriptors of expected behaviours through an iterative process: testing of the scale on 10 FC transcripts by two experts, soliciting feedback from a focus group of seven health care providers, and testing by non-experts on 49 live FCs. In phase 3, scores on the revised scale were validated by 10 health care providers from different disciplines by rating three videos of FCs of variable quality. Raters were able to detect inter-video variation in FC quality. The reliability of the FCRS was 0.95 and the inter-rater reliability, 0.68. The FCRS may enhance the ability of health professions educators to teach and assess interprofessional patient-centred communication and collaboration competencies.